Infecção por Salmonella Heidelberg em Pintos de Corte Alimentados com Dietas Contendo Compostos Bioativos Comerciais - Silva, Raíssa Almeida (2018)
More than 2.600 serotype of Salmonella spp. A known today, and salmonellosis in humans may be related to the consumption contaminated of poultry eggs, as well as causing disease in poultry, causing a decrease in production and consequently increasing proff loss. Salmonella Heidelberg is an emerging and worrying serotype for poultry and public health, and is more invasive when compared to other paratyphoid serotypes. The use of antimicrobials used for therapeutic and prophylactic purposes in the control of Salmonella spp. in poultry production may lead to the selection of resistant bacterial strains; however, its use in animal production may be replaced by alternative products capable of reducing the incidence of enteropathogens, providing beneficial effects on host health. Chapter 1 sought to evaluate the effect of the bioproduct added to the feed, in order to decrease Salmonella Heidelberg multiplication. The intestinal colonization and systemic infection were evaluated through colony counts by CFU / g in cecal, liver and spleen contents, as well as the evaluation of macroscopic and microscopic alterations at 3, 7 and 14 dpi in liver, cecum and ileum and the ileus histomorphometric parameters such as height of villi, depth of crypt, villus: crypt and villus area in cut chicks challenged with Salmonella Heidelberg were measured.The lowest cecal SH counts were observed in birds that ingested sanguinarin, followed by those fed with XPC (P> 0.05). There was no synergistic effect on SH reduction in the cecum when both bioproducts were added simultaneously (SANG + XPC). Mean scores for SH in liver and spleen did not differ between groups (P> 0.05). In general, birds from all groups challenged with HS presented similar macroscopic alterations such as hemorrhagic areas, hepato and splenomegaly; such changes were more discrete at 14 dpi. Microscopic changes observed in liver included congestion of hepatocytes, infiltration of heterophiles in the sinusoids, necrosis areas of mononuclear xii inflammation. While in the cecum, heterophilic infiltrates and thickening of lamina propria could be observed. In the ileum the most frequent changes were congestion of lamina propria, atrophy of villi, atrophy of crypt and thickening of lamina propria. It was observed that the intensity of microscopic changes was lower in the birds supplemented with the bioproducts, when compared to the infected control group. Birds supplemented with sanguinarine were the ones that developed the least changes. In the histomorphometric parameters of the ileum, it was generally observed throughout the study, higher mean height and villus area in birds from the uninfected control group and also from the SANG group. While the crypt depth was lower in birds of the negative control group. In the present study, the results indicate that the addition of bioproducts, mainly sanguinarin, in the diet of birds assisted in the control of SH infection, reducing its count in cecal content and improving aspects of bird general and intestinal health.